Development of Snake and Ladder Board Game Media to Improve Fifth-Grade Students Learning Outcomes on Fraction - Putri, Yulia Melinda; Andaryani, Eka Titi (Jurnal Pendidikan Progresif, 2025)
Development of Snake and Ladder Board Game Media to Improve Fifth-Grade Students Learning Outcomes on Fraction. Objective: This study aims to develop a game-based snake and ladder learning media to improve the learning outcomes of fractional mathematics in grade 5 elementary school students. Methods: Research and Development (R&D) is the type of research used. The research design applied is ADDIE design, which consists of five stages: analysis, design, development, implementation, and evaluation. The data collection techniques used in this study consisted of test and non-test techniques. Test techniques include pre-test and post-test, while non-test techniques include observation, interviews, questionnaires, and documentation. Findings: Based on the validation results by media experts and material experts, the following results were obtained: the assessment from media experts was 91.25% (very feasible), and the evaluation of material experts was 89.70% (very feasible). The assessment of the two experts shows that the snake and ladder game media is worth using. The data analysis techniques used in this study consisted of normality tests, T-tests, and N-Gain tests. The normality test results showed that the significance value (Sig.) > 0.05 means the data was normally distributed. Based on the T-test on a small scale and a large scale, a Sig. (2-tailed) value of 0.000 was obtained, showing a significant difference between the use of snake and ladder game media and the learning outcomes of grade 5 students. Furthermore, the N-Gain result for the small scale is 0.71, and for the large scale, it is 0.76; both results are included in the high category. Conclusion: Thus, based on the results of data analysis, snake and ladder game media has been proven to be effective in mathematics learning to improve learning outcomes in fractional materials as well as as a fun educational tool, especially in the context of 21st-century learning that emphasizes collaboration skills, creativity, critical thinking, and communication (4C). This media increases students’ motivation and facilitates active learning through a game-based learning approach. Snake and ladder can be adapted for various subjects by modifying the content of the questions or challenges according to the needs of the curriculum. Keywords: snake and ladder, learning outcomes, fraction.